Denim casual wear with laser cut pucuk rebung motif / Husna Saaidin and Rosita Mohd Tajuddin - Saaidin, Husna; Mohd Tajuddin, Rosita (Universiti Teknologi MARA, 2018)
This study explored the use of laser cutting technology on denim casual wear inspired by the pucuk rebung motif. The objective of this study was to examine the suitability of laser cutting technique application on denim casual wear using pucuk rebung motif. Several experiementations of laser cutting applied on pucuk rebung motifs were conducted on various types of denim fabrics to identify strength, durability while maintaining the aesthetic of pucuk rebung motif on denim casual wear. Four denim casual wears were designed with the placement of the the motifs on different areas of the fabric. Pucuk rebung motifs were simplified to allow the application of the laset cutting on the motif. A post test was performed to verify which design that would preferred most by the target audience. All respondents agreed that the used of laser cutting on pucuk rebung motif applied on denim casual wear was appropriate and able to create an interesting surface design. Results from this study proved that traditional Malay motifs could be applied and enhanced into casual wear using laser cutting as an innovative way uplifting the traditional motif on contemporary design besides enhancing the unique Malaysian culture via fashion.